Dealing with host and food searching in a diurnal parasitoid: consequences of light at night at intra‐ and trans‐generational levels. Issue 2 (16th March 2021) - Gomes, Elisa; Rey, Benjamin; Débias, François; Amat, Isabelle; Desouhant, Emmanuel
Abstract: Light pollution is a widespread phenomenon with major consequences on nocturnal organisms from individual to community. However, its effects on diurnal organisms are still scarcely studied. We exposed diurnal parasitoid wasps ( Venturia canescens ) to low (0.7 lux) or high (20 lux) artificial light for two to eight consecutive nights, and quantified its consequences on their physiology and daytime behaviour compared to a control group (0 lux). We next considered potential trans‐generational effects on offspring whose mothers were exposed to light pollution. While in the dark night the wasps showed no activity, exposure to artificial light triggered nocturnal activity and altered diurnal behaviours related to foraging. Wasps exposed to light at night had a greater propensity to choose hosts rather than food compared to controls. They also spent more time feeding when exposed to 0.7 lux of light at night. However, these behavioural modifications were not related to changes in individual energy reserves. Light pollution effects persisted at trans‐generational level: offspring development time and latency before feeding increased when mothers were exposed to 0.7 lux light at night. Even at low intensity, light pollution alters foraging behaviour of a diurnal insect. Searching for hosts or food being essential for fitness, light pollution is likely to have long‐term repercussions on insect populations. Light pollution caused behavioural modifications potentially beneficial for V. canescens in the short term. However, longer term studies (e.g. on lifetime reproductive success) are needed to fully understand its consequences on insects. Abstract : We studied whether low and high intensity of light exposure at night affect the physiology and behaviour of the diurnal parasitoid wasp Venturia canescens, at intra‐ and trans‐generational levels. Wasps exposed to light pollution became nocturnally active. Light at night also increased the propensity to choose hosts rather than food and time spent feeding during the daytime. Exposure of mothers to low intensity of light at night increased offspring development time and latency before feeding at trans‐generational level.